Cardiomyogenic differentiation potential of human lipoaspirate-derivedstem cells on hyaluronic acid/gelatin plasma gels - (:unkn) unknown (My University, 2016)
0

Cardiomyogenic differentiation from mesenchymal stem cells has emerged as a novel approach for repair of damaged myocardium. Cell transplantation through direct cell injection is not an optimal method due to the lack of cell-extracellular matrix interactions. In the present study, differentiation potential of human adipose-derived stem cells (ASCs) to cardiomyocytes has been investigated by growing them on hyaluronic acid/gelatin (HA/G) plasma gels and coverslips and supplementing the growth medium with chemical modifiers (activin-a, BMP-4, insulin, valproic acid, and 5-azacytidine) in various combinations. The HA/G plasma gels were produced from human blood plasma-derived fibrinogen, gelatin, and human umbilical cord-derived hyaluronic acid. A network-based approach was employed to select marker genes for cardiomyogenic differentiation, and the expression levels of three markers (GATA4, TBX5, and cTnI) were followed by RT-qPCR to investigate the cardiomyogenic differentiation potential of ASCs. Results indicated that each combination of chemical modifiers led to different expression levels in the aforementioned cardiac markers, and this was material-dependent, too. The cardiac gene expression on HA/G plasma gels in the presence of activin-a + BMP-4 or insulin + valproic acid was more pronounced than in the presence of 5-azacytidine only, and scaffold and chemical modifier combinations were crucial for cardiomyogenic differentiation.
Keywords: Biyoloji